Frequency of Thrombocytosis in Iron Deficiency Anemia - Aamna Liaqat, Nadia Tufail, Nabeeia Liaqat, Syeda Hussan E Zahra, Tariq Iqbal, Fariha Liaqat (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of thrombocytosis in iron deficiency anemia Study Design: A Cross sectional survey. Study Setting: Pediatric Department of Mayo Hospital, Lahore Study Duration: 20-07-2019 to 19-01-2020. Methods: 181 children meeting the inclusion criterion were included in study and 2-3 ml of venous blood was drawn and sent to lab for complete blood count (CBC). Data regarding the MCV, MCH, Platelet count was collected on structured Performa. Results: Significant association was seen in age and thrombocytosis in cases of IDA (p<0.05). There is a highly significant association between anemia, sex and thrombocytosis in the cases of IDA (p<0.01). Conclusion: There is association between thrombocytosis and iron deficiency anemia in pediatric age group.